STRATEGY USED BY THE ENGLISH DEBATERS OF UKM BAHASA UNIVERSITAS MUHAMMADIYAH MAKASSAR IN DEVELOVING THEIR SPEAKING SKILL - Andi Mutiara Sari; Andi Tenri Ampa; Wildhan Burhanuddin (FKIP Unismuh Makassar, 2022)
This research aimed to find out the learning strategy are used by English Debaters in Speakng Skill at UKM BAHASA Universitas Muhammadiyah and the reason why do the English debaters use those strategy. The data were collected in July 2022 from 5 debaters of UKM BAHASA Universitas Muhammadiyah Makassar. This research used a descriptive qualitative method, and the instruments used an interview. The findings of this research show that learning strategy are used by English Debaters in Speakng Skill at UKM BAHASA Universitas Muhammadiyah are Watching video on YouTube, Read articles, Group discussion, Self-correction, and Self-talk strategy. The result of the interview of this research showed that mostly the reason why do debaters used those strategies because the strategies are easy to access, easy to imitiate and they can do wherever and whenever they wants to enjoy it.